Targeting Endothelial Adhesion Molecule Transcription for Treatment of Inflammatory Disease: A Proof-of-Concept Study - Liam M. Ashander; Binoy Appukuttan; Yuefang Ma; Dione Gardner-Stephen; Justine R. Smith (Hindawi Limited, 2016)
Targeting the endothelial adhesion molecules that control leukocyte trafficking into a tissue has been explored as a biological therapy for inflammatory diseases. However, these molecules also participate in leukocyte migration for immune surveillance, and inhibiting the physiological level of an adhesion molecule might promote infection or malignancy. We explored the concept of targeting endothelial adhesion molecule transcription during inflammation in a human system. Intercellular adhesion molecule 1 (ICAM-1) mediates leukocyte migration across the retinal endothelium in noninfectious posterior uveitis. We observed an increase in the transcription factor, nuclear factor of kappa light polypeptide gene enhancer in B-cells 1 (NF-κB1), in parallel with ICAM-1, in human retinal endothelial cells treated with tumor necrosis factor-alpha (TNF-α), and identified putative binding sites for NF-κB1 within the ICAM-1 regulatory region. We targeted induced NF-κB1 expression in endothelial cells with small interfering (si)RNA. Knockdown of NF-κB1 significantly decreased cell surface expression of ICAM-1 protein induced by TNF-α but did not reduce constitutive ICAM-1 expression. Consistently, NF-κB1 knockdown significantly reduced leukocyte binding to cell monolayers in the presence of TNF-α but did not impact baseline binding. Findings of this proof-of-concept study indicate that induced transcription of endothelial adhesion molecules might be targeted therapeutically for inflammatory disease in humans.